Application of Clavien–Dindo classfication-grade in evaluating overall efficacy of laparoscopic pancreaticoduodenectomy - Song, Xiangyang; Ma, Yu; Shi, Hongyun; Liu, Yahui (Frontiers in Surgery, 2023)
Background The Clavien–Dindo classification (CDC) has been widely accepted and applied in clinical practice. We investigated its effectiveness in prediction of major complications (LPPC) after laparoscopic pancreaticoduodenectomy (LPD) and associated risk factors. Methods A retrospective analysis was conducted covering clinical data of 793 patients undergoing LPD from April 2015 to November 2021. CDC was utilized to grade postoperative complications and analyze the differences. Risk factors of LPPC were identified according to univariate and multivariate analyses. Resluts For the 793 patients undergoing laparoscopic pancreaticoduodenectomy in the northeast of China, LPPC was reported in 260 (32.8%) patients, pancreatic fistula in 169 (21.3%), biliary fistula in 44 (5.5%), delayed gastric emptying in 17(2.1%), post pancreatectomy hemorrhage in 55 (6.9%), intestinal fistula in 7 (0.8%), abdominal infections in 59 (7.4%) and pulmonary complication in 28 (3.5%). All complications were classified into five levels with the C–D classification (Grade I–V), with 83 (31.9%) patients as grade I, 91 (35.0%) as grade II, 38 (14.6%) as grade IIIa, 24 (9.2%) as grade IIIb, 9 (3.5%) as grade IV and 15 (5.8%) as grade V. 86 (10.8%) patients experienced major complications (grade III–V).The results of univariate and multivariate analysis revealed the independent risk factors for laparoscopic pancreaticoduodenectomy complications to be preoperative total bilirubin (P = 0.029, OR = 1.523), soft pancreas texture (P < 0.001, OR = 1.399), male (P = 0.038, OR = 1.396) and intraoperative transfusion (P = 0.033, OR = 1.517). Preoperative total bilirubin (P = 0.036, OR = 1.906) and intraoperative transfusions (P = 0.004, OR = 2.123) were independently associated with major postoperative complications. The influence of different bilirubin levels on C–D grade of complications was statistically significant (P = 0.036, OR = 1.906). Conclusions The Clavien–Dindo classification (CDC) may serve as a valid tool to predict major postoperative complications and contribute to perioperative management and comparison of surgical techniques in different medical centers.